Evaluation of an integrated control scheme against Rhipicephalus (Boophilus) microplus in pregnant cows and in cows with calf in northeastern Argentina (FAVE Sección Ciencias Veterinarias, 2022)
The aim was to evaluate an integrated control scheme for Rhipicephalus (Boophilus) microplus in pregnant and calving cows combining two treatments with chemical acaricides and paddock rest in a representative locality of northeastern Argentina. This scheme was designed to combine the therapeutic effect of strategic control (two treatments applied between late winter and spring) with the rest of pastures (in the present work of three months) on the amount of larvae present in a paddock. Twenty-two Braford-type heifers and cows were divided into two groups in paddocks naturally infested with ticks, with a rest of three months before the animals were admitted. Group I received two acaricidal treatments with fluazuron and flumethrin and group II remained without treatment as a control group. Tick ​​infestation was monitored monthly and therapeutic efficacy was calculated. The infestation with Rhipicephalus (Boophilus) microplus in group I was significantly lower than that of the control group and the efficacy levels were always higher than 93%, with the exception of the February count, where the efficacy was 89.1%. The complementary integration of the partial decontamination applied through a three-month pasture rest with a strategic treatment scheme (two in a 10-month period) allowed reaching significant levels of efficacy in the control of Rhipicephalus (Boophilus) microplus while maintaining low levels of infestation with minimal movements to management pens, and providing sustainability to the use of acaricides.
Keywords: ticks; control; Argentina; pregnant cows